The Assessment of Factors and Forecast of Labor Productivity in the Manufacturing Industry of the Tambov Oblast - Elena Yurina; Alexander Kostylev; Yana Kulikova; Tatiana Cheremisina (Communications of International Proceedings, 2020)
The article discusses labor productivity indicators in the manufacturing industry of the Tambov Oblast. The study identifies the factors that affect labor productivity and conducts a correlation analysis. As a result of the analysis, the determining factor is defined – demographic. The forecast of labor productivity in the Tambov Oblast for the period up to 2024 is made using the method of time-series extrapolation.
Keywords: Correlation Analysis; Labor Productivity; Regional Management.